Chile : Proposal for an Arrangement Under the Short-Term Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Chile. - International Monetary Fund. Western Hemisphere Dept.. (Washington, D.C. : International Monetary Fund, 2022)
The Chilean economy has rapidly recovered from the fallout of the Covid-19 pandemic, thanks to an impressive vaccination campaign and effective policy support. The authorities will continue leveraging on Chile's very strong fundamentals and policy frameworks to safeguard the recovery, preserve macroeconomic stability, and boost inclusive and green growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Chile